Preparation method and application of MoS2 / CoS2 / NiS-CC electrocatalytic material
MoS2/CoS2/NiS-CC composite material was prepared by hydrothermal method and low-temperature vulcanization method to form a three-dimensional rod-shaped heterostructure, solving the problem of easy destruction of MOF at high temperatures, and achieving efficient electrochemical hydrogen evolution catalysis and stability improvement.
Patent Information
- Application Number
- CN202411901241.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, MOF, as the precursor of the electrocatalytic material, is easily destroyed at high temperatures, is prone to agglomeration and difficult to grow during the sintering process, resulting in a decrease in the porosity of the material and a decrease in the electrocatalytic activity.
MoS2/CoS2/NiS-CC composite material was prepared by hydrothermal method and low-temperature vulcanization method through cobalt-nickel MOF and molybdenum source to form a three-dimensional rod-shaped heterostructure, and the heterointerface was used to accelerate the charge transfer at the interface and reduce the energy barrier of the HER electrocatalytic process.
It realizes efficient electrochemical hydrogen evolution catalysis, improves electrolytic efficiency and stability, and has rich pores and high-density active sites, which are suitable as an efficient electrochemical hydrogen evolution catalyst.
Smart Images

Figure CN119753739A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalysis, and specifically relates to a preparation method and application of a MoS2 / CoS2 / NiS-CC electrocatalytic material. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the increasing demand for energy in modern society, the limited reserves of fossil fuels, and the increasing public concern about environmental issues, clean and efficient hydrogen energy has been widely studied. The electrocatalytic decomposition of water to produce hydrogen is a strong uphill reaction. The use of efficient electrocatalysis for the hydrogen evolution reaction (HER) can effectively improve the reaction kinetics and greatly reduce the overpotential. Currently, the most efficient HER electrocatalyst is Pt-based precious metal catalyst, but its high cost, low stability and limited natural reserves have greatly restricted the application and development of fuel cells. Therefore, the development of cheap, efficient and stable non-precious metal catalysts to reduce the amount of Pt has become a research hotspot.
[0004] Porous carbon materials are ideal precursors for the preparation of functional materials. They have the characteristics of large specific surface area, uniform pore structure, rigid framework, good thermal stability and excellent chemical properties. They are widely used in the fields of adsorption, catalysis and electrochemistry. Metal-Organic Frameworks (MOFs) are a type of ordered 3D crystalline materials with a periodic network structure formed by the self-assembly of inorganic metal centers and bridging organic ligands. They are different from both inorganic porous materials and general organic complexes, and have the rigidity of inorganic materials and the flexibility of organic materials. Compared with traditional porous materials, MOFs have unique advantages such as high porosity, structural diversity, easy functionalization, high specific surface area and good designability. Unfortunately, although MOF can be used alone as an electrocatalytic material, it has problems such as poor stability and weak activity. In order to solve the above problems, a variety of heteroatom-doped porous carbon materials with MOF as a precursor have been reported. They not only have the ultra-high specific surface area, different pore size distribution and ordered porous structure of the original MOF, but also enhance the conductivity and stability, and have good catalytic activity for processes such as anode hydrogen evolution reaction. However, in the prior art, MOF is usually used as a sacrificial template to prepare electrocatalytic materials by pyrolysis and calcination, while the structure of MOF is easily destroyed at high temperature, and it is easy to agglomerate and difficult to grow during the sintering process, which reduces the porosity of the final material and reduces the electrocatalytic activity. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the present invention provides a MoS2 / CoS2 / NiS-CC composite material with excellent electrocatalytic performance. This material is obtained by hydrothermal method and low-temperature sulfurization method of cobalt-nickel MOF and molybdenum source. The MoS2 / CoS2 / NiS-CC electrocatalytic material has a three-dimensional rod-shaped heterostructure.
[0006] First, the present application provides a MoS2 / CoS2 / NiS-CC electrocatalytic material, which has the following diffraction angles 2θ of MoS2 in the X-ray diffraction pattern: 4.07°, 33°, 58.8°, the following diffraction angles 2θ of CoS2: 32.6°, 36.2°, 46.2° and 54.9°, and the following diffraction angles 2θ of NiS: 32.2°, 35.5° and 50.2°.
[0007] Preferably, the electrocatalytic material is a three-dimensional rod-shaped heterostructure with an average particle size of 40 to 50 μm.
[0008] The electrocatalytic effect of this material is closely related to the particle size. In this scheme, the particle size of the MoS2 / CoS2 / NiS-CC material is preferably within 50 μm. Too large a size will affect the electrocatalytic effect.
[0009] The above-mentioned electrocatalytic materials form a heterogeneous structure between MoS2, CoS2 and NiS on the surface. The heterogeneous interface accelerates the interfacial charge transfer, thereby reducing the energy barrier of the HER electrocatalytic process and improving the electrolysis efficiency and stability.
[0010] Preferably, the MoS2 / CoS2 / NiS-CC electrocatalytic material in the present application is prepared by the following method:
[0011] S1, reacting nickel salt and cobalt salt with organic ligand in a solution containing carbon cloth to obtain Co-Ni MOF-CC;
[0012] S2, placing Co-Ni MOF-CC, molybdenum salt, ammonium fluoride and thioacetamide in a hydrothermal reactor of polytetrafluoroethylene to react and obtain a MoS2 / CoS2 / NiS-CC precursor;
[0013] S3. The MoS2 / CoS2 / NiS-CC precursor is reacted with a sulfur source to fully sulfurize to obtain a MoS2 / CoS2 / NiS-CC electrocatalytic material.
[0014] Preferably, in step S1, the organic ligand is dimethylimidazole.
[0015] In this scheme, the mechanism of using dimethylimidazole to synthesize MOF is that dimethylimidazole can affect the nucleation rate of crystals through competitive coordination with the bridging ligand. This competitive coordination can inhibit the growth of MOFs in the vertical direction, thereby preparing MOFs with special morphology and size. The special MOF structure can provide a stable growth template for subsequent materials and increase the growth area, which can not only expose more active sites, but also promote the diffusion of electrolyte on the catalyst surface and accelerate the HER reaction process. At the same time, compared with single metal MOF, bimetallic MOF can expose more active sites, which is conducive to the improvement of catalytic activity.
[0016] Preferably, in step S1, the nickel salt is any number of nickel nitrate and nickel chloride, and the cobalt salt is any number of cobalt nitrate, cobalt chloride and cobalt sulfate. Further preferably, in step S1, the molar ratio of the nickel salt to the cobalt salt is 2:3.
[0017] Preferably, in step S2, the molybdenum salt comprises molybdate. Further preferably, in step S2, the molar ratio of the molybdenum salt, ammonium fluoride and thioacetamide is 1:0.4-0.6::1.5-3.
[0018] Preferably, in step S3, the sulfur source is any number of sulfur powder and thioacetamide.
[0019] In addition, the present application also relates to the application of the above-mentioned MoS2 / CoS2 / NiS-CC electrocatalytic material.
[0020] The present invention has the following beneficial effects:
[0021] 1. The MoS2 / CoS2 / NiS-CC electrocatalytic material of the present invention is obtained by a simple hydrothermal method and a low-temperature sulfurization method. The prepared composite electrocatalyst with a three-dimensional heterogeneous structure has abundant pores and high-density active sites and can be used as an efficient electrochemical hydrogen evolution catalyst. The preparation method is simple to operate, the reaction conditions are easy to achieve, and it has industrial application prospects.
[0022] 2. A heterogeneous structure is formed between MoS2, CoS2 and NiS on the surface of the MoS2 / CoS2 / NiS-CC electrocatalytic material. The heterogeneous interface accelerates the interfacial charge transfer, thereby reducing the energy barrier of the HER electrocatalytic process and improving the electrolysis efficiency and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image of the MoS2 / CoS2 / NiS-CC catalytic material in Example 1.
[0024] Figure 2This is the transmission electron microscopy image of MoS2 / CoS2 / NiS-CC in Example 1.
[0025] Figure 3 This is a high-resolution transmission electron microscopy image of MoS2 / CoS2 / NiS-CC in Example 1.
[0026] Figure 4 It is the XRD spectrum of the MoS2 / CoS2 / NiS-CC catalytic material prepared by the present invention.
[0027] Figure 5 a) Hydrogen evolution polarization curve (LSV) of different catalyst materials in the hydrogen evolution reaction process in alkaline electrolyte; b) HER overpotential value; c) LSV curve of MoS2 / CoS2 / NiS-CC before and after 5000 CV cycles; d) Tafel slope diagram.
[0028] Figure 6 a) LSV curve of different catalyst materials in the hydrogen evolution reaction process in acidic electrolyte; b) HER overpotential value; c) LSV curve of MoS2 / CoS2 / NiS-CC before and after 5000 CV cycles; d) Tafel slope diagram. DETAILED DESCRIPTION
[0029] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The technical scheme of the present invention is further described below in conjunction with embodiments. The following embodiments are only used to illustrate the present invention, but are not intended to limit the scope of the present invention in any form.
[0031] Example 1
[0032] A method for preparing a MoS2 / CoS2 / NiS-CC electrocatalytic material specifically comprises the following steps:
[0033] Pretreatment steps: first, the carbon cloth was cut into a size of 1 cm×2 cm, and then it was placed in 2 mmol / L nitric acid, deionized water and ethanol for ultrasonic treatment for 30 minutes to remove the surface oxide layer, and then placed in a blast dryer for drying.
[0034] S1: Preparation of Co-Ni MOF-CC: Weigh 1g of dimethylimidazole and pour it into a beaker, then dissolve it with 10mL of deionized water, recorded as solution A, weigh 0.4g of nickel nitrate hexahydrate and 0.6g of cobalt nitrate hexahydrate respectively, pour them into the same beaker, and then dissolve them with 15mL of deionized water, recorded as solution B. Take out the dried carbon cloth, put it into solution A, soak it for 3min, slowly pour solution B into solution A and stir it with a glass rod for several times to make the drugs fully contact, finally stand it at room temperature for 10-12h, take it out, rinse the surface of the carbon cloth with deionized water, put it in a drying oven to dry and remove it, and you can get the purple Co-Ni MOF-CC.
[0035] S2: Preparation of MoS2 / CoS2 / NiS-CC precursor: 1mmol of sodium molybdate, 0.5mmol of ammonium fluoride and 2mmol of thioacetamide were placed in a 50ml polytetrafluoroethylene hydrothermal reactor, and 15ml of deionized water was added to allow the drugs to be fully mixed and dissolved, and finally Co-Ni MOF-CC was placed in an oven at 200°C for 16h. After the hydrothermal reactor was cooled naturally to room temperature, the carbon cloth was taken out, rinsed with deionized water to remove the residual drugs on the surface, and dried in a vacuum drying oven to obtain MoS2 / CoS2 / NiS-CC precursor.
[0036] S3: Preparation of MoS2 / CoS2 / NiS-CC: Take 1g of sulfur powder as the sulfur source and place it in the upstream area of the porcelain boat. Place the dried MoS2 / CoS2 / NiS-CC precursor in the downstream area of the porcelain boat and heat it to 450℃ in the insulation zone of the tubular furnace at a heating rate of 3℃ per minute. Keep it warm for 2h to allow the precursor to be fully sulfurized to obtain MoS2 / CoS2 / NiS-CCC electrocatalytic material, recorded as sample 1.
[0037] The morphology of the MoS2 / CoS2 / NiS-CC electrocatalytic material obtained in Example 1 was observed using a scanning electron microscope. Figures 1 to 3 As shown, it is demonstrated that the MoS2 / CoS2 / NiS-CC electrocatalytic material was successfully prepared in the embodiment of the present invention.
[0038] The electrocatalytic material is further characterized by X-ray diffraction (XRD). Figure 4As shown, the diffraction angles (2θ) of 14.07°, 33°, and 58.8° correspond to the (002), (100), and (110) crystal planes of MoS2 (PDF#75-1539), respectively; CoS2 (PDF#89-1492) has peaks at 2θ=32.6°, 36.2°, 46.2°, and 54.9°, corresponding to the (200), (210), (220), and (311) crystal planes, respectively; and peaks also appear at 2θ=32.2°, 35.5°, and 50.2°, representing the (-211), (-111), and (-2-13) crystal planes of NiS (PDF#75-0612), respectively. The XRD analysis results confirmed the presence of three substances, MoS2, CoS2 and NiS, in the material prepared in Example 1, which provided more reaction active centers, confirming that the present invention successfully synthesized the MoS2 / CoS2 / NiS-CC heterostructure material.
[0039] Comparative Example 1: This comparative example is a pretreated commercial Pt electrode. The specific steps are: the Pt electrode is placed in 2mmol / L nitric acid, deionized water and ethanol in turn for 30 minutes of ultrasound to remove the surface oxide layer, and then placed in a blower dryer for drying.
[0040] The HER performance of the above-mentioned Example 1 and the comparative example was tested using an electrocatalytic test system: In the test, a standard three-electrode working system was used, with Example 1 and the comparative example prepared in the present invention as the working electrode, a saturated calomel electrode as the reference electrode, and a carbon rod electrode as the counter electrode. The alkaline electrolyte was a 1M KOH solution, and the acidic electrolyte was a 0.5M H2SO4 solution. The HER activity of Example 1 and the comparative example prepared in the present invention was tested using linear sweep voltammetry.
[0041] Figure 5 The polarization curves and Tafel slope diagrams obtained from the HER linear sweep voltammetry test under alkaline conditions are shown. Figure 5 (a) and 5(b) show that the overpotential of MoS2 / CoS2 / NiS-CC material at a current density of 10mA / cm2 is 62mV, while the overpotential of Pt commercial electrode is 57mV. Figure 5 As shown in (c), after 5,000 CV cycles of MoS2 / CoS2 / NiS-CC, an LSV curve is obtained. Compared with the previous LSV, it can be seen that after 5,000 CV cycles, the electrochemical performance of the sample has not changed much, and the sample can also maintain long-term stability at 100,000s, indicating that MoS2 / CoS2 / NiS-CC has good hydrogen evolution stability. In addition, from Figure 5(d) shows the Tafel slope. It can be seen that the MoS2 / CoS2 / NiS-CC material has a very low Tafel slope (71.3 mV / dec), indicating faster kinetic characteristics.
[0042] Figure 6 The polarization curves and Tafel slope diagrams obtained from the HER linear sweep voltammetry test under acidic conditions are shown. Figure 6 (a) and 6(b) show that the overpotential of MoS2 / CoS2 / NiS-CC material at a current density of 10mA / cm2 is 41mV, while the overpotential of Pt commercial electrode is 35mV. Figure 6 As shown in (c), under acidic conditions, when the current density is 100mA / cm2, the overpotential of MoS2 / CoS2 / NiS-CC material reaches 269mV, which is lower than the commercial Pt electrode (460mV). Figure 6 (d) shows the Tafel slope. It can be seen that the MoS2 / CoS2 / NiS-CC material has a very low Tafel slope (77.0 mV / dec), indicating faster kinetic characteristics.
[0043] From the above data, it can be seen that the overpotential of the MoS2 / CoS2 / NiS-CC electrocatalytic material is very close to the overpotential of the precious metal Pt commercial electrode, and the kinetic characteristics are faster. And compared with the alkaline hydrogen evolution performance of other similar electrocatalytic materials reported, the present invention shows a lower overpotential (as shown in Table 1 and Table 2). This shows that the MoS2 / CoS2 / NiS-CC electrocatalytic material of the present invention has excellent HER performance and has good commercial application value.
[0044] Embodiment 2,
[0045] This embodiment provides a method for preparing a MoS2 / CoS2 / NiS-CC electrocatalytic material, which specifically includes the following steps:
[0046] The amount of ammonium fluoride in step S2 of Example 1 was changed to 0.4 mmol; the temperature in step S3 was changed to 500° C., and the other steps and amounts of reactants were exactly the same as in Example 1.
[0047] Embodiment 3,
[0048] This embodiment provides a method for preparing a MoS2 / CoS2 / NiS-CC electrocatalytic material, which specifically includes the following steps:
[0049] The amount of ammonium fluoride in step S2 in Example 1 was changed to 0.6 mmol, and the other steps and amounts of reactants were exactly the same as in Example 1.
[0050] Embodiment 4,
[0051] This embodiment provides a method for preparing a MoS2 / CoS2 / NiS-CC electrocatalytic material, which specifically includes the following steps:
[0052] The amount of thioacetamide in step S2 of Example 1 was changed to 1.5 mmol, and the other steps and amounts of reactants were exactly the same as in Example 1.
[0053] Embodiment 5,
[0054] This embodiment provides a method for preparing a MoS2 / CoS2 / NiS-CC electrocatalytic material, which specifically includes the following steps:
[0055] The amount of thioacetamide in step S2 of Example 1 was changed to 35 mmol, and the other steps and amounts of reactants were exactly the same as those in Example 1.
[0056] In addition, the following electrocatalytic material was prepared for comparison of hydrogen evolution performance under alkaline environment with the electrocatalytic material in the present application.
[0057] Control Example 2, the electrocatalytic material prepared by the method in reference to Zhang Y, Shi M, Wang C, et al. Vertically aligned NiS2 / CoS2 / MoS2 nanosheet array as an efficient and low-cost electrocatalyst for hydrogen evolution reaction in alkaline media[J]. Science Bulletin, 2020, 65(5): 359-366.
[0058] Reference Example 3: The electrocatalytic material prepared by the method in reference to Zhang L, Zheng Y, Wang J, et al. Ni / Mo bimetallic-oxide-derived heterointerface-rich sulfide nanosheets with co-doping for efficient alkaline hydrogen evolution by boosting volmer reaction[J]. Small, 2021, 17(10): 2006730.
[0059] Control Example 4: An electrocatalytic material prepared by the method in reference to Tao K, Gong Y, Lin J. Low-temperature synthesis of NiS / MoS2 / C nanowires / nanoflakes as electrocatalyst for hydrogen evolution reaction in alkaline medium via calcining / sulfurizing metal-organic frameworks [J]. Electrochimica Acta, 2018, 274: 74-83.
[0060] The comparison of hydrogen evolution performance of the electrocatalytic material in this example and comparative examples 2 to 4 under alkaline conditions is shown in Table 1.
[0061]
[0062] The following electrocatalytic material was prepared for comparison of hydrogen evolution performance in an acidic environment with the electrocatalytic material in the present application.
[0063] Control Example 5: An electrocatalytic material was prepared by the method in reference to Kendall L, Lin Q, Zangari G, et al. Electrodeposited heterostructures of cobalt sulfide / molybdenum sulfide trigger both acidic and alkaline HER[J]. Journal of The Electrochemical Society, 2023, 170(4): 042501.
[0064] Control Example 6, an electrocatalytic material prepared by the method in reference to Hu J, Zhang C, Yang P, et al. Kinetic-oriented construction of MoS2 synergistic interface to boost pH-universal hydrogen evolution [J]. Advanced Functional Materials, 2020, 30(6): 1908520.
[0065] For control example 7, an electrocatalytic material was prepared according to the method in Huang N, Ding Y, Yan S, et al. Ultrathin MoS2 nanosheets vertically grown on CoS2 acicular nanorod arrays: a synergistic three-dimensional shell / core heterostructure for high-efficiency hydrogen evolution at full pH [J]. ACS Applied Energy Materials, 2019, 2(9): 6751-6760.
[0066] The comparison of hydrogen evolution performance of the electrocatalytic material in this example and comparative examples 5 to 7 under acidic conditions is shown in Table 2.
[0067]
[0068] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A MoS2 / CoS2 / NiS-CC electrocatalytic material, characterized in that: In its X-ray diffraction pattern, the diffraction angles 2θ of MoS2 are as follows: 4.07°, 33°, 58.8°, the diffraction angles 2θ of CoS2 are as follows: 32.6°, 36.2°, 46.2° and 54.9°, and the diffraction angles 2θ of NiS are as follows: 32.2°, 35.5° and 50.2°.
2. A MoS2 / CoS2 / NiS-CC electrocatalytic material according to claim 1, characterized in that: The electrocatalytic material is a three-dimensional rod-shaped heterogeneous structure with an average particle size of 40 to 50 μm.
3. The MoS2 / CoS2 / NiS-CC electrocatalytic material according to claim 1, characterized in that: Prepared by the following method: S1, reacting nickel salt and cobalt salt with organic ligand in a solution containing carbon cloth to obtain Co-Ni MOF-CC; S2, placing Co-Ni MOF-CC, molybdenum salt, ammonium fluoride and thioacetamide in a hydrothermal reactor of polytetrafluoroethylene to react and obtain a MoS2 / CoS2 / NiS-CC precursor; S3. The MoS2 / CoS2 / NiS-CC precursor is reacted with a sulfur source to fully sulfurize to obtain a MoS2 / CoS2 / NiS-CC electrocatalytic material.
4. The MoS2 / CoS2 / NiS-CC electrocatalytic material according to claim 3, characterized in that: In step S1, the organic ligand is dimethylimidazole.
5. The MoS2 / CoS2 / NiS-CC electrocatalytic material according to claim 3, characterized in that: In step S1, the nickel salt may be any number of nickel nitrate and nickel chloride, and the cobalt salt may be any number of cobalt nitrate, cobalt chloride and cobalt sulfate.
6. The MoS2 / CoS2 / NiS-CC electrocatalytic material according to claim 3, characterized in that: In step S1, the molar ratio of the nickel salt to the cobalt salt is 2:
3.
7. The MoS2 / CoS2 / NiS-CC electrocatalytic material according to claim 3, characterized in that: In step S2, the molybdenum salt includes molybdate.
8. The MoS2 / CoS2 / NiS-CC electrocatalytic material according to claim 2, characterized in that: In step S2, the molar ratio of the molybdenum salt, ammonium fluoride and thioacetamide is 1:0.4-0.6::1.5-3.
9. The MoS2 / CoS2 / NiS-CC electrocatalytic material according to claim 2, characterized in that: In step S3, the sulfur source is any number of sulfur powder and thioacetamide.
10. The use of a MoS2 / CoS2 / NiS-CC electrocatalytic material according to claim 1, characterized in that: Applied in the field of electrocatalytic water decomposition to produce hydrogen.